Frequent MYD88 L265P and CD79B Mutations in Primary Breast Diffuse Large B-Cell Lymphoma. (March 2016) - Taniguchi, Kohei; Takata, Katsuyoshi; Chuang, Shih-Sung; Miyata-Takata, Tomoko; Sato, Yasuharu; Satou, Akira; Hashimoto, Yuko; Tamura, Maiko; Nagakita, Keina; Ohnishi, Nobuhiko; Noujima-Harada, Mai; Tabata, Tetsuya; et al.
Abstract : Primary breast diffuse large B-cell lymphoma (PB-DLBCL) is a rare disease comprising <3% of extranodal lymphomas. It frequently reveals an activated B-cell (ABC)-like phenotype. ABC-like DLBCL was reported to have gain-of-function mutations in MYD88, CD79B, CARD11, and TNFAIP3, resulting in constitutive activation of the NFκB pathway. Because of the rare occurrence of PB-DLBCL, the frequency of MYD88 and CD79B mutations is still unknown. We used Sanger sequencing to study these mutations from 46 breast DLBCL cases and also investigated the associated clinicopathologic factors. MYD88 L265P was confirmed by allele-specific polymerase chain reaction and compared with the Sanger sequencing results. MYD88 L265P and CD79B mutations were detected in 27/46 (58.7%) and 11/33 (33.3%) cases, respectively. Twenty-eight of 46 cases met the criteria for PB-DLBCL, and the latter 18 cases were further classified as clinical breast DLBCL (CLB-DLBCL). The frequency of MYD88 L265P and CD79B mutations was 16/28 (57.1%) and 9/23 (39.1%), respectively, in PB-DLBCL and 11/18 (61.1%) and 2/10 (20%), respectively, in CLB-DLBCL. When the cutoff value was set at ΔCt⩽1, the result of allele-specific polymerase chain reaction for MYD88 corresponded to those of the Sanger sequence at 92.6% sensitivity and 100% specificity. According to Choi's algorithm, 16/27 (59.3%) demonstrated an ABC-like phenotype in PB-DLBCL, and 15/18 (83.3%) demonstrated an ABC-like phenotype in CLB-DLBCL. In conclusion, MYD88 L265P and CD79B mutations were frequently detected in PB-DLBCL, and they may be key molecules associated with PB-DLBCL lymphomagenesis. Further analysis will be required to clarify the mechanism of its pathogenesis. Abstract : Supplemental Digital Content is available in the text.